The Role of Card Acceptance in the Transaction Demand for Money - Kim P. Huynh; Philipp Schmidt-Dengler; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2014)
The use of payment cards, either debit or credit, is becoming more and more widespread in developed economies. Nevertheless, the use of cash remains significant. We hypothesize that the lack of card acceptance at the point of sale is a key reason why cash continues to play an important role. We formulate a simple inventory model that predicts that the level of cash demand falls with an increase in card acceptance. We use detailed payment diary data from Austrian and Canadian consumers to test this model while accounting for the endogeneity of acceptance. Our results confirm that card acceptance exerts a substantial impact on the demand for cash. The estimate of the consumption elasticity (0.23 and 0.11 for Austria and Canada, respectively) is smaller than that predicted by the classic Baumol-Tobin inventory model (0.5). We conduct counterfactual experiments and quantify the effect of increased card acceptance on the demand for cash. Acceptance reduces the level of cash demand as well as its consumption elasticity.
Keywords: E41; C35; C83; 330; Inventory models of money; counterfactual distributions; endogenous switching regressions; Kreditkarte; Geldnachfragetheorie; Bargeld; Konsumentenverhalten; Elastizität; Schätzung; Österreich; Kanada